2010
DOI: 10.1128/cmr.00070-09
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Diagnosis, and Antimicrobial Treatment of Acute Bacterial Meningitis

Abstract: SUMMARY The epidemiology of bacterial meningitis has changed as a result of the widespread use of conjugate vaccines and preventive antimicrobial treatment of pregnant women. Given the significant morbidity and mortality associated with bacterial meningitis, accurate information is necessary regarding the important etiological agents and populations at risk to ascertain public health measures and ensure appropriate management. In this review, we describe the changing epidemiology of bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
679
3
47

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 723 publications
(754 citation statements)
references
References 362 publications
(591 reference statements)
25
679
3
47
Order By: Relevance
“…Community-acquired bacterial meningitis is a severe infectious disease with high morbidity and mortality rates (Brouwer et al 2010), and is most commonly caused by Streptococcus pneumoniae (van de Beek et al 2004b). Acquired immunodeficiency previously has been associated with an increased risk of bacterial meningitis (Adriani et al 2013;van Veen et al 2016;Weisfelt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Community-acquired bacterial meningitis is a severe infectious disease with high morbidity and mortality rates (Brouwer et al 2010), and is most commonly caused by Streptococcus pneumoniae (van de Beek et al 2004b). Acquired immunodeficiency previously has been associated with an increased risk of bacterial meningitis (Adriani et al 2013;van Veen et al 2016;Weisfelt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…No homologous sequence of those molecules was detected in Ccs4. Despite abundant epidemiological data that S. pneumoniae is the most common cause of bacterial meningitis [3], only four pneumococcal factors have been reported to contribute to BBB penetration. Furthermore, NanA, CbpA, and RrgA are not considered to be competence-inducible molecules [25].…”
Section: Discussionmentioning
confidence: 99%
“…Infection with the Gram-negative bacterium E. coli is also an important cause of bacterial meningitis [3], and the transmembrane proteins, such as OmpA [31] and YijP [32], contribute to hBMEC adhesion and invasion. OmpA loops, which mediate bacterial entry into hBMECs, have been identified [31,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries of the African ‘meningitis belt’ have for over 100 years experienced large meningococcal meningitis epidemics [24]. Multilocus sequence typing (MLST) of carriage and disease isolates has shown that between the late 1980s and 2010, epidemic waves of colonization and disease were mainly associated with hypervirulent serogroup A clones with the sequence types (ST) 5, 7, and 2859 [58].…”
Section: Introductionmentioning
confidence: 99%